Analyzing the Effectiveness of Performance Appraisal in BKD Batam: Implementation, Challenges, and Supporting Factors in SKP and Job Descriptions - Muhammad Rafi Juanda; Lubna Salsabila; Karol Teovani Lodan; Timbul Dompak (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
The goal of democratic reform is to build an efficient and effective government management structure. Good governance, reflected from top to bottom, is demonstrated through the efficiency of civil servants in a country. This research focuses on the Badan Kepegawaian Daerah (BKD) of Batam City, as its performance reports reveal issues in evaluating employee performance. While BKD Batam has adhered to Government Regulation No. 46 of 2011 on Employee Performance Appraisal in the Execution of Official Duties, the current evaluation method is not effectively implemented. This regulation is expected to contribute positively by assisting government agencies in assessing the performance of their employees. The study combines qualitative methodology with a descriptive field research approach and inductive theoretical perspective. The aim is to describe and analyze the effectiveness of performance appraisal at BKD Batam, along with identifying the factors that hinder effective evaluation. Using interactive data analysis techniques, the findings conclude that BKD Batam's current performance evaluation system is ineffective due to its lack of integration with established standards and performance indicators. The key factors hindering effective performance evaluation include: 1) the subjective nature of the current evaluation; 2) the improper placement of civil servants in positions not aligned with their educational background; 3) the lack of strong understanding regarding the importance of performance evaluation among both evaluators and those being evaluated; and 4) a decline in supervision during the performance evaluation process.